Emotions and the British government’s decision for war in 1914 - Young, John (Taylor & Francis (Routledge), 2018)
Recent years have witnessed increasing interest among international historians in the impact of emotions on foreign policy decisions, as part of a broader movement usually known as the ‘emotional turn.’ This is associated with findings, from the field of neuroscience, that cognition and emotion – rather than operating independently – are inextricably bound together in human decision-making Most work thus far has concentrated on American foreign policy since 1945, but this article broadens the focus to consider the impact of emotions on British decision-makers, especially Cabinet ministers, as they debated whether to go to war in 1914. It shows that, despite a tendency by the protagonists themselves to interpret their actions in rational terms, sufficient evidence of emotions can be found in the written record to allow a fresh approach to be taken to the July Crisis. While emotions must be seen as acting alongside rational mental processes, rather than regularly overpowering them, a focus on the subject helps explain different approaches taken by individual ministers, why the majority came to approve intervention in the conflict and how the Prime Minister, H. H. Asquith, partly by appearing to control his feelings, minimised resignations over the fateful decision. It also allows a new view to be taken of why the Cabinet decided to go to war on 4 August in defence of Belgium, despite deciding just a few days earlier that the question of fulfilling the 1839 guarantee of Belgian neutrality was ‘one of policy than of legal obligation.’